Pengembangan Modul Berbasis Nilai Karakter pada Subtema Indahnya Persatuan dan Kesatuan Negeriku di Sekolah Dasar - Saputri, Rini Hendri; Ramadan, Zaka Hadikusuma (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to develop a character value-based module in the sub-theme of the beauty of the unity and integrity of my country and to determine the validity of the module based on character values ​​in the sub-theme of the beauty of the unity and integrity of my country in the fourth grade of elementary school. This type of research is development research using the ADDIE model. Data analysis techniques in this study are qualitative and quantitative description analysis techniques. The methods used in data collection are interviews, validation, and documentation. The results of the study show that the percentage of validation by material experts is 89%, design experts are 91.33% and linguists are 96%. The conclusion from this study is that character value-based modules are appropriate for use in the learning process.